Implementation of new normal policies during the COVID-19 pandemic in Southeast Sulawesi, Indonesia - Abas, Abas; Asma, Asma; Wa Zul, Wa Zul; Irmawati, Irmawati; Alhajar, Hayatun Nufusi (YCAB Publisher & IAKMI SULTRA, 2021)
Background: The new normal policy during the COVID-19 pandemic needs public involvement. Efforts to reduce the number of COVID-19 cases require the public to understand the knowledge, attitudes, and behavior of COVID-19 prevention health protocols.Objective: This research aimed to assess knowledge, attitudes, and practices towards the prevention of COVID-19.Methods: This was descriptive research conducted in Muna District on June 2021 with 410 respondents. Data collection was carried out using a questionnaire and provided online through WhatsApp groups and social media using Google Forms.Results: Most of the respondents answered knowing the cause of COVID-19 (82.4%), COVID-19 transmission (54.4%), prevention by using masks (81.0%), washing hands (83.9%), social distancing (86.8%), and cough etiquette (81.2%). People's attitudes towards opinions about COVID-19 vary. Disagree with the statement that someone who buys products from China can contract COVID-19 (51.0%), agree on spraying disinfectants (37.6%), opinions that are uncertain eucalyptus, garlic, and sesame oils can prevent transmission of COVID-19 (52.4%), views that disagree COVID-19 is the same as the common cold (73.2%), respondents are Uncertain that COVID-19 can be treated with antibiotics (42.9%), respondents answered